Rapid and Visual Detection of Trichinella Spp. Using a Lateral Flow Strip-Based Recombinase Polymerase Amplification (LF-RPA) Assay - Li, Ting-Ting; Wang, Jin-Lei; Zhang, Nian-Zhang; Li, Wen-Hui; Yan, Hong-Bin; Li, Li; Jia, Wan-Zhong; Fu, Bao-Quan (Frontiers in Cellular and Infection Microbiology, 2019)
ABSTRACT Trichinella spp., are amongst the most widespread parasitic nematodes, primarily live in the muscles of a wide range of vertebrate animals and humans. Human infection occurs by ingestion of raw or undercooked meat containing Trichinella larvae. Accurate diagnosis of Trichinella spp. infection in domestic animals is crucial for the effective prevention and control of human trichinellosis. In the present study, a simple, rapid and accurate diagnostic assay was developed combining recombinase polymerase amplification and a lateral flow strip (LF-RPA) to detect Trichinella spp. infection. The LF-RPA assay targets Trichinella spp. mitochondrial small-subunit ribosomal RNA (rrnS) gene and can detect as low as 100 fg DNA of Trichinella strains, which was approximately 10 times more sensitive than a conventional PCR assay. The LF-RPA assay can be performed within 10-25 min, at a wide range of temperatures (25- 45 °C) and showed no cross-reactivity with DNA of other parasites and related host species of Trichinella. The performance of the LF-RPA assay in the presence of high concentration of PCR inhibitor was better than that of a conventional PCR assay. Results obtained by LF-RPA assay for the detection of experimentally infected mice were comparable to the results obtained by using a conventional PCR, achieving 100% specificity and high sensitivity. These results present the developed LF-RPA assay as a new simple, specific, sensitive, rapid and convenient method for the detection of Trichinella infection in domestic animals.